The Unavoidable Palm Oil Can Be Sustainable - GH YUE; Baoqing Ye; Antonius A Suwanto (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2020)
The oil palm is the most productive oil-producing crop. To yield the same volume of oil that is from one hectare of palm, eight hectares of soybean are needed. Palm oil is used an ingredient in over 50% of packaged supermarket products and also as biofuels. The palm oil sector provides over 4.5 million jobs for on-farm laborers in developing countries. However, palm oil is often blamed for deforestation and loss of biodiversity. We argue that palm oil sustainability is not only about the environment and biodiversity but also about people and their prosperity. Palm oil sustainability can be achieved with joint efforts from palm oil players including the smallholders, plantation companies, governments, certification agencies, consumers and researchers.